1972
DOI: 10.1111/j.1600-0714.1972.tb02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive lesions of the gingiva

Abstract: Abstract. A total of 279 cases of reactive lesions of the gingiva have been subdivided into three groups: pyogenic granuloma/gingival fibromatoid lesions, peripheral giant cell granuloma and peripheral ossifying fibroma. Age, sex and and site distribution are similar for pyogenic granuloma/ gingival fibromatoid lesions and peripheral giant cell granuloma; namely, comparable bimodal age peaks occur, women are affected more often, and a predilection exists for the anterior segment of the dental arch. Although p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
176
3
8

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(197 citation statements)
references
References 8 publications
5
176
3
8
Order By: Relevance
“…Oral hygiene maintenance instructions were also given. A recurrence rate of 20% has been reported, mainly due to incomplete removal of the lesion and/or persistence of aetiological factors [9]. However, there has not been any recurrence of the lesion, two years post operatively.…”
Section: Introductionmentioning
confidence: 98%
“…Oral hygiene maintenance instructions were also given. A recurrence rate of 20% has been reported, mainly due to incomplete removal of the lesion and/or persistence of aetiological factors [9]. However, there has not been any recurrence of the lesion, two years post operatively.…”
Section: Introductionmentioning
confidence: 98%
“…The etiology of the peripheral ossifying fibroma is unknown, although some authors have suggested that the lesion is associated with inflammatory hyperplasia of the periodontal ligament [4,8]. Others speculate about a possible hormonal influence since prepubertal patients are rarely affected and the disease incidence falls significantly after the third decade of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, the lesion consists of fibrous proliferation associated with formation of mineralized tissue, which can resemble both cement and dystrophic calcification. When former is observed, the lesion is called peripheral cemento ossifying fibroma [4,5]. The objective of the present article is to report a case of POF occurring in the maxillary anterior region of a 13 year old girl.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations